2023
DOI: 10.1038/s41467-023-41686-9
|View full text |Cite
|
Sign up to set email alerts
|

Myelination and excitation-inhibition balance synergistically shape structure-function coupling across the human cortex

Panagiotis Fotiadis,
Matthew Cieslak,
Xiaosong He
et al.

Abstract: Recent work has demonstrated that the relationship between structural and functional connectivity varies regionally across the human brain, with reduced coupling emerging along the sensory-association cortical hierarchy. The biological underpinnings driving this expression, however, remain largely unknown. Here, we postulate that intracortical myelination and excitation-inhibition (EI) balance mediate the heterogeneous expression of structure-function coupling (SFC) and its temporal variance across the cortica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…We calculated the region-wise Hurst exponent value, a metric that is mathematically related to the 1/f exponent of neural signals 21,56 and used as an index of the E/I ratio. As previously described, 5,57 resting-state fMRI time series were modeled as multivariate fractionally integrated processes, and the Hurst exponent was estimated via the univariate maximum likelihood method and discrete wavelet transform. 5 As such, an elevated E/I ratio would manifest in a lower Hurst exponent value.…”
Section: Hurst Exponent Reductions In Tlementioning
confidence: 99%
“…We calculated the region-wise Hurst exponent value, a metric that is mathematically related to the 1/f exponent of neural signals 21,56 and used as an index of the E/I ratio. As previously described, 5,57 resting-state fMRI time series were modeled as multivariate fractionally integrated processes, and the Hurst exponent was estimated via the univariate maximum likelihood method and discrete wavelet transform. 5 As such, an elevated E/I ratio would manifest in a lower Hurst exponent value.…”
Section: Hurst Exponent Reductions In Tlementioning
confidence: 99%
“…Evidence indicates that the structure-function relationship is not uniform across brain regions, pointing to a more robust coupling in the unimodal cortex, which is sensitive to immediate changes in the sensory environment, and a weaker association in the transmodal cortex, which is sensitive to a prior context [26,27,28,29,30,31]. It has been suggested that this regional heterogeneity may potentially reflect underlying molecular and cytoarchitectural gradients, highlighting a hierarchy of time scales of intrinsic fluctuations across the cortex [2,32,33,34,35,36]. Moreover, it was reported that the structure-function relationship is modality-dependent, suggesting that functional connections estimated from longer time windows overlap significantly with the underlying structural connections.…”
Section: Introductionmentioning
confidence: 99%